ROLE OF WOMEN IN INDIAN JUDICIARY AND WOMEN EMPOWERMENT- A REVIEW (International Journal of Food and Nutritional Sciences, 2022)
One essential characteristic of democracies is diversity. India is one of several democracies without a justice system that adequately represents the diversity of the nation. Most of the judges serving on India's Supreme and High Courts are cisgender men from upper castes. This unifies the viewpoints of justice and law. Inadequate institutional and infrastructure support, discrimination, harassment, and gender stereotypes are just a few of the structural obstacles that women judges and attorneys must overcome. A few of the elements that lead to various types of oppression include sexual orientation, caste, class, and religious identity. By analysing them critically via a number of feminist perspectives, we highlight the ingrained and unconscious biases that contribute to the disproportionately low percentage of female judges. Next, we suggest modifying the institutional framework to help promote diversity in India's courts. The paper explores how women have historically been portrayed in the legal system before talking about what gender "objectivity" implies when it comes to making choices. The final segment will look at the overall effect of having women on the court as well as opportunities for reform in the way that women's issues are addressed, in light of recent historic verdicts on gender discrimination and equal rights.